Characterizing and quantifying weak chaos in fractional dynamics - Borin, Daniel [UNESP]; Szezech, José Danilo; Sales, Matheus Rolim [UNESP] (Elsevier, 2025)
A particularly intriguing and unique feature of fractional dynamical systems is the cascade of bifurcations type trajectories (CBTT). We examine the CBTTs in a generalized version of the standard map that incorporates the Riemann–Liouville fractional derivative, known as the Riemann–Liouville Fractional Standard Map (RLFSM). We propose a methodology that uses two quantifiers based solely on the system’s time series: the Hurst exponent and the recurrence time entropy, for characterizing such dynamics. This approach allows us to effectively characterize the dynamics of the RLFSM, including regions of CBTT and chaotic behavior. Our analysis demonstrates that regions of CBTT are associated with trajectories that exhibit lower values of these quantifiers compared to strong chaotic regions, indicating weakly chaotic dynamics during the CBTTs.